2023
DOI: 10.1130/ges02581.1
|View full text |Cite
|
Sign up to set email alerts
|

Critical workforce skills for bachelor-level geoscientists: An analysis of geoscience job advertisements

Abstract: Understanding the skills bachelor-level geoscientists need to enter the workforce is critical to their success. The goal of this study was to identify the workforce skills that are most requested from a broad range of geoscience employers. We collected 3668 job advertisements for bachelor-level geoscientists and used a case-insensitive, code-matching function in Matlab to determine the skills geoscience employers seek. Written communication (67%), field skills (63%), planning (53%), and driving (51%) were most… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We assigned each ad an occupation as defined by the U.S. Bureau of Labor Statistics 2018 Standard Occupational Classification Systems (U.S. Bureau of Labor Statistics, 2018) and an industry sector as defined by the 2018 American Geosciences Institute (AGI) Status of the Geoscience Workforce Report (Wilson, 2019). Additional details about the collection and classification of the job advertisements are described by Shafer et al (2023). When making comparisons among ads for different occupations, we only include occupations with >50 advertisements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assigned each ad an occupation as defined by the U.S. Bureau of Labor Statistics 2018 Standard Occupational Classification Systems (U.S. Bureau of Labor Statistics, 2018) and an industry sector as defined by the 2018 American Geosciences Institute (AGI) Status of the Geoscience Workforce Report (Wilson, 2019). Additional details about the collection and classification of the job advertisements are described by Shafer et al (2023). When making comparisons among ads for different occupations, we only include occupations with >50 advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…We created a third criterion to categorize how well a requested physical ability matched the core job description (Table 3). We used the case-insensitive, code-matching model and search criteria employed by Shafer et al (2023) to identify which ads from the set of 2,518 requested physical abilities. Our initial analysis indicated that driving was the most commonly requested physical ability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation